Catalogue of the Hyperidean Amphipoda (Crustacea) of the Southern Ocean with distribution and ecological data - Zeidler W.; De Broyer, C. (In: De Broyer C. (ed.), Census of Antarctic Marine Life, Synopsis of the Amphipoda of the Southern Ocean. Bulletin de l'Institut Royal des Sciences Naturelles de Belgique, Biologie, 2009)
A catalogue of hyperiidean amphipods (Crustacea: Peracarida: Amphipoda) recorded from the Southern Ocean is established including full synonymy, complete distribution records and bibliographical references. The catalogue comprises 74 described species but only 15 have a distribution restricted to the region between the Subtropical Convergence and the Antarctic Continent, which is presented on maps. The remainder are widely distributed in nearly all of the world’s oceans. Detailed information on geographical and bathymetric distribution in the Southern Ocean and information on the worldwide distribution is given for each species. Details on the type locality and location of type-material is also provided. Another 20 species that have been recorded south of 40°S but not in the Southern Ocean as defined here, are not included in the catalogue but are listed in an Appendix for future reference. Identification tools currently available for hyperiids are summarized in another Appendix. The catalogue is based on taxonomic and ecological literature checked until 28 February 2009. Some unpublished species records from the Southern Ocean (determined by WZ) in various museum collections have also been included.